Palliative care during COVID-19: Data and visits from loved ones - Heath, L; Yates, S; Carey, M; Miller, M (SAGE Publications, 2020)
Objectives: A vital component of the coronavirus response is care of the dying COVID-19 patient. We document the demographics, symptoms experienced, medications required, effectiveness observed, and challenges to high-quality holistic palliative care in 31 patients. This will aid colleagues in primary and secondary care settings anticipate common symptoms and formulate management plans. Methods: A retrospective survey was conducted of patients referred to the hospital palliative care service in a tertiary hospital, south east of England between March 21 and April 26, 2020. Patients included had a confirmed laboratory diagnosis of COVID-19 via reverse transcription polymerase chain reaction nasopharyngeal swab for SARS-Cov-2 or radiological evidence of COVID-19. Results: The thirty-one patients included were predominantly male (77%), elderly (median [interquartile range]: 84 [76-89]), and had multiple (4 [3-5]) comorbidities. Referral was made in the last 2 [1-3] days of life. Common symptoms were breathlessness (84%) and delirium (77%). Fifty-eight percent of patients received at least 1 “as required” dose of an opioid or midazolam in the 24 hours before death. Sixty percent of patients needed a continuous subcutaneous infusion and the median morphine dose was 10 mg S/C per 24 hours and midazolam 10 mg S/C per 24 hours. Nineteen percent of our cohort had a loved one or relative present when dying. Conclusion: We provide additional data to the internationally reported pool examining death arising from infection with SARS-CoV-19. The majority of patients had symptoms controlled with low doses of morphine and midazolam, and death was rapid. The impact of low visitation during dying needs exploring.